Variable Length Cyclic Prefix OFDM Using Multipath Delay Tracking - Abdulrahman Ikram Siddiq (Tikrit Journal of Engineering Sciences, 2013)
The Cyclic Prefix (CP) technique is widely used in Orthogonal Frequency Division Multiplexing (OFDM) systems. A CP of length greater than the channel order guarantees the orthogonality of the consecutive OFDM symbols. Therefore, the effects of Inter Symbol Interference (ISI) and Inter Carrier Interference (ICI) are cancelled. On the other hand, CP reduces the transmission efficiency. Conventional OFDM systems use constant length CP. For time varying channels, CP length may become shorter than channel order resulting in considerable loss in orthogonality and performance degradation. Otherwise, when CP length becomes much greater than channel order it results with time and power wasting, and hence decreasing transmission efficiency. This paper proposes the usage of a multipath delay tracking module to provide the OFDM system with the actual channel order and accordingly the suitable CP length will be determined. Computer simulations show that the proposed system saves about 47.6% of the time and power spent by the same constant length CP OFDM system tested under the same conditions.